A retrospective study: establishment and validation of the prediction model for the gonadotropin starting dose in IVF/ICSI-ET among normal ovarian response women - Zhang, Yindi; Zhang, Na (Frontiers in Endocrinology, 2025)
PurposeThis study aims to create and validate a clinical prediction model to determine the optimal gonadotropin (Gn) starting dose in controlled ovarian stimulation (COS) protocols for normal ovarian response (NOR) patients undergoing their first IVF/ICSI-ET cycle.MethodsA retrospective analysis was conducted based on the data of the first IVF/ICSI-ET cycles of 535 patients from the Reproductive Medicine Department of the Fourth Hospital of Hebei Medical University between January 2017 and June 2024. The patients were randomly divided into a training group (n=317) and a validation group (n=218) in a 6:4 ratio. Linear regression analysis was applied to screen out the potential factors influencing the Gn starting dose, and the statistically significant factors were selected to construct a nomogram for Gn dosage. We used an internal verification method to ensure the reliability of the nomogram.ResultsThe patient’s age, body mass index (BMI), basal follicle-stimulating hormone (bFSH), antral follicle count (AFC), and anti-Müllerian hormone (AMH) were predictive indicators of the Gn starting dose for NOR patients undergoing IVF/ICSI-ET treatment (P<0.05). A predictive model was created based on the above indicators. Finally, the accuracy of this predictive model was validated by comparing the actual Gn starting doses with the predicted doses in both the training and the validation group. The results showed no significant difference between the actual and predicted Gn starting doses in the two groups (P>0.05).ConclusionBased on age, BMI, bFSH, AMH, and AFC, a clinician could determine the patient’s appropriate Gn starting dose for NOR patients undergoing IVF/ICSI-ET.